Her heart's desire [large type] - Gray, Shelley Shepard (Gray, Shelley Shepard. Season in Pinecraft, 2023)
"A wallflower in her Amish community, Mary Margaret hopes a trip will offer her a chance to come out of her shell. When a chance meeting brings new friends and a gentle young man into her life, she imagines a whole new life in Florida. But will it all disappear once vacation ends?"--